2006
DOI: 10.1161/01.hyp.0000205119.19804.08
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension, Diabetes, and Cardiovascular Disease Risk in a Population-Based Sample

Abstract: Abstract-There are few data about the impact of the recently-defined category of prehypertension (systolic blood pressure 120 to 139 mm Hg or diastolic blood pressure 80 to 89 mm Hg) on cardiovascular disease incidence. It is also unknown whether this association differs between individuals with or without diabetes. A total of 2629 Strong Heart Study participants free from hypertension and cardiovascular disease at baseline examination were followed for 12 years to observe incident cardiovascular disease. Appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
137
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(158 citation statements)
references
References 23 publications
15
137
3
3
Order By: Relevance
“…Many cross-sectional studies of different populations demonstrated that prehypertensive individuals had higher total cholesterol, LDL-C, TG and lower HDL-C than normotensive subjects [6][7][8][20][21][22][23][24][25][26][27][28][29][30] . Some prospective studies also showed that dyslipidemia could predict occurrence of incident hypertension by years [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cross-sectional studies of different populations demonstrated that prehypertensive individuals had higher total cholesterol, LDL-C, TG and lower HDL-C than normotensive subjects [6][7][8][20][21][22][23][24][25][26][27][28][29][30] . Some prospective studies also showed that dyslipidemia could predict occurrence of incident hypertension by years [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…A study of 1999 to 2000 NHANES data has suggested that 64% of prehypertensive subjects have ≥1 other abnormal CVD risk factors, the percentage increased to 94% in those ≥60 years of age 6 . The risk ratios for obesity, dyslipidemia, metabolic syndrome, and diabetes are all greater in prehypertensive than normotensive subjects 7,8 . The dyslipidemias represent heterogenic metabolic disorders.…”
Section: Introductionmentioning
confidence: 96%
“…Its treatment is one of the major risk factors for the development of cardiovascular disease, stroke, and the end stage of renal disease (Zhang et al, 2006). Among the processes associated with hypertension, angiotensin I converting enzyme (ACE) plays an important role in the regulation of blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Estos resultados son muy similares a los obtenidos en el estudio The Strong Heart Study 2006, donde la prehipertensión fue más frecuente en menores de 60 años que en los de mayor edad, sobre todo si los sujetos padecen concomitantemente diabetes mellitus. En este estudio se demostró que la intolerancia a la glucosa o la alteración de la glucosa en ayunas aumentan en gran medida el 45 riesgo de enfermedad cardiovascular en personas prehipertensas.…”
Section: Discussionunclassified